Achieving safety and productivity in construction projects. Issue 2 (17th February 2017) - Choudhry, Rafiq Muhammad
Abstract: Improvement of safety and productivity are major concerns throughout the construction industry. There is a dearth of efforts that document the need for simultaneous achievement of safety and productivity on construction sites. The objective of this research is to investigate productivity and safety simultaneously on construction projects by conducting a survey. In total, 1, 800 hard-copy questionnaires were distributed and the response rate was 81%, resulting in 1, 454 valid questionnaires for analysis. Safety and productivity were investigated on 25 construction projects by means of statistical analysis. The results indicated that eleven of the fifteen significant findings pertained to safety and the rest to productivity. The results confirmed that it is possible to improve productivity and safety simultaneously on construction projects. All measures were found to be correlated with both safety and productivity. The findings of this research provide practical knowledge to project managers and safety practitioners on construction projects to achieve safety and productivity simultaneously. The methodology of research might be useful for research at other construction projects in other regions and cultures.